Molecular characterization of Treponema pallidum subsp. pallidum in Switzerland and France with a new multilocus sequence typing scheme - Grillová, Linda; Bawa, Tanika; Mikalová, Lenka; Gayet-Ageron, Angèle; Nieselt, Kay; Strouhal, Michal; Sednaoui, Patrice; Ferry, Tristan; Cavassini, Matthias; Lautenschlager, Stephan; Dutly, Fabrizio; Pla-Díaz, Marta; et al. (PloS one, 2018)
Syphilis is an important public health problem and an increasing incidence has been noted in recent years. Characterization of strain diversity through molecular data plays a critical role in the epidemiological understanding of this re-emergence. We here propose a new high-resolution multilocus sequence typing (MLST) scheme for Treponema pallidum subsp. pallidum (TPA). We analyzed 30 complete and draft TPA genomes obtained directly from clinical samples or from rabbit propagated strains to identify suitable typing loci and tested the new scheme on 120 clinical samples collected in Switzerland and France. Our analyses yielded three loci with high discriminatory power: TP0136, TP0548, and TP0705. Together with analysis of the 23S rRNA gene mutations for macrolide resistance, we propose these loci as MLST for TPA. Among clinical samples, 23 allelic profiles as well as a high percentage (80% samples) of macrolide resistance were revealed. The new MLST has higher discriminatory power compared to previous typing schemes, enabling distinction of TPA from other treponemal bacteria, distinction between the two main TPA clades (Nichols and SS14), and differentiation of strains within these clades.
Keywords: Multilocus Sequence Typing; RNA, Ribosomal, 23S; France; Švýcarsko; Genotype; fylogeneze; Sequence Analysis, DNA; Phylogeny; antibakteriální látky; sekvenční analýza DNA; Genome, Bacterial; Francie; jednonukleotidový polymorfismus; syfilis; RNA ribozomální 23S; genom bakteriální; DNA, Bacterial; DNA bakterií; Treponema pallidum; Polymorphism, Single Nucleotide; Anti-Bacterial Agents; Switzerland; Globus Pallidus; multilokusová sekvenční typizace; Syphilis; Macrolides; genotyp; globus pallidus; makrolidy; Alleles; alely